Higher Education, Happiness, and Residents' Health - Tan, Hong; Luo, Jin; Zhang, Ming (Frontiers in Psychology, 2020)
The study proposes another mechanism by which higher education affects the health of residents, believing that higher education can improve the happiness of residents and thus improve their health condition. Based on data collected in Chinese General Social Survey (2013) and the semi-parametric estimation method of ordered probit model, it is found that, compared with the residents who did not receive higher education, residents who received high education do have better health condition, and residents' happiness also significantly affects their health condition. Moreover, higher education may have a long-term impact on residents' health by affecting their happiness. The results of grouping test show that, with the increase of age, the influence of residents' happiness on health is more obvious, and the mechanism of higher education to improve health status by improving residents' happiness is more obvious. Furthermore, Shapley value decomposition method was used to decompose the influence of various factors on residents' health. The results show that, with the growth of age, happiness contributes more and more to residents' health status, which also verified the age effect of higher education on health to some extent.